Early life factors and COVID-19 infection in England: A prospective analysis of UK Biobank participants. (April 2021) - Didikoglu, Altug; Maharani, Asri; Pendleton, Neil; Canal, Maria Mercè; Payton, Antony
Abstract: This study aims to examine whether maternal smoking, birth weight, birth month and breastfeeding are associated with COVID-19 infection and hospitalisation. Maternal smoking was positively associated with COVID-19 infection. Breastfeeding was negatively associated with COVID-19 infection. The odds of being hospitalised due to COVID-19 were higher among those who had lower birthweight and mothers who were smoking during pregnancy. Highlights: Low birth weight was associated with hospitalisation due to COVID-19. The odds of contracting COVID-19 were 12% lower among respondents who were breastfed when they were babies. People who reported that their mother smoked when they were born had 20% higher odds of COVID-19 infection and 24% higher odds of hospitalisation.